The relationship between cognitive maladaptive schemes and self-esteem in adolescents - Sandu, Mihaela; Călin, Mariana Floricica; Mogos, Nicoleta (Technium Social Sciences Journal, 2021)
The motivation for choosing this topic is based on our desire to understand how the cognitive patterns formed in the early periods of adolescent development, influence and affect the formation and development of self-esteem during adolescence. Adolescence is a crucial and critical period in the development of the individual, a period of transition between childhood and adulthood, and self-esteem plays a very important role for the development of the individual during this period. Self-esteem is an important part of our personality that includes two significant elements - self-knowledge and self-awareness. This includes the individual’s perceptions of himself, his strengths and weaknesses, his abilities, attitudes and values. Its development begins at birth and develops constantly under the influence of experiences. In different age periods that children go through, they become aware of their skills and practical abilities in the first place - motor skills, artistic skills, performance skills, etc. The mental development of the adolescent is largely determined by the family. Love and trust, competent answers and advice are the fundamental "tool" of parents who help their children become autonomous and competent adults.